APPRAISAL OF THE STUDIES ON MATURATION AND SPAWNING IN MARINE TELEOSTS FROM THE INDIAN WATERS - Qasim, S Z (Indian Journal of Fisheries, 2011)
Maturation and spawing in many teleosts from the Indian waters have been studiedby different authors using conventional methods. The most common among thesemethods are seasonal changes in the condition of gonads and the ova diameter frequencydistribution. The latter is supposed to give an index of the progression of oocytes andtheir withdrawal from the ovaries. There are several drawbacks in these methods, asthey were essentially developed for fishes from the temperate regions. It is thereforedesirable that other methods should also be used for arriving at a realistic picture of thespawning process. Maturity is clearly linked with the growth rate of fishes and hencethe two phases—pre-and post-maturity—should be clearly distinguished. Spawning ina population is possibly geared to external events, when conditions for the newlyproduced broods are most favourable. Fishes in the Indian waters spawn in all themonths of the year, but along the east coast spawning largely seems to occur during thepre-monsoon months and along the west coast during the monsoon and post-monsoonmonths. Many species appear to be continuous breeders, and hence to develop a clearunderstanding of their maturation and spawning, it is necessary to make observationsthroughout the year.